Antithrombotic activity of flavonoids and polyphenols rich plant species - Bojić Mirza; Maleš Željan; Antolić Andrea; Babić Ivana; Tomičić Maja (Acta Pharmaceutica)
Cardiovascular diseases represent one of the most notable health problems of the modern civilization. Stroke and heart attack often lead to lethal outcome; essential problem underneath being thrombus formation. Prophylactic approaches include acetylsalicylic acid and clopidogrel therapy on the level of primary hemostasis, i.e., primary clot formation. In the last five years, in the USA, health care expenses related to cardiovascular diseases have increased 50 %, to over 350 billion dollars. Thus, application of plant species and medicinal plants rich in polyphenols in prevention of thrombus formation are of interest. This is supported by the fact that the number of publications on antiaggregatory effect of polyphenols has doubled in the last decade. In this review we focus on antiaggregatory effect of most abundant polyphenols – flavonoids, the effect of plant extracts rich in polyphenols (propolis, species Salvia sp., Calamintha nepeta L., Lavandula angustifolia Mill., Melissa officinalis L, Mentha x piperita L., Ocimum basilicum L., Origanum vulgare L., Rosmarinus officinalis L.) on platelet aggregation, association of chemical composition and antioxidant properties with the observed biological effect, and possible clinical significance of the published results.